β-lactamase genes in clinical isolates of Capnocytophaga canimorsus and description of a novel class D β-lactamase, OXA-1422 - Zoja Germuskova; Eleonora Pronzini; Fanny Wegner; Tim Roloff; Tianyan Song; Miroslava Barancekova; Alois Cizek; Michael Addidle; Murray Robinson; Marc Dieu; Chaitanya Tellapragada; Christian G. Giske; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Why Was the Official Australian Monsoon Onset Unusually Late in 2024/25? - Tim Cowan; Rajashree Naha; Hanh Nguyen; Hanna Heidemann; Sugata Narsey; Matthew C. Wheeler; Corey Robinson; Chris Lucas; Andrew G. Marshall; Lin Wang (Advances in Atmospheric Sciences, 2026)
The official 2024/25 Australian summer monsoon (ASM) onset occurred on 7 February, more than two weeks later than the previous record. Defined using Darwin winds, the official ASM typically arrives between mid-December and mid-January. Here, we investigate (1) why the ASM onset was record late, despite La Niña-like conditions, and (2) if the late ASM onset was consistent with other unofficial monsoon and rainy season onset definitions. Our results show earlier onsets when using wind and rainfall-based definitions, mainly due to strong synoptic-to-intraseasonal variability. Two onset definitions were triggered in December 2024 when the Madden–Julian Oscillation (MJO) contributed to deep convection and above-average rain over northern Australia. In late January, a monsoon trough formed over northeast and northwest Australia, but not over Darwin. With the MJO in a suppressed state, the Darwin region experienced record-breaking January temperatures. The ASM eventually arrived in early February, with the reason behind its historically late onset likely a result of weather noise and variability. Another location, ∼1200 km east of Darwin, did not experience such a late onset, using similar definitions. Relevant to monsoon systems globally, our study highlights the limitations of local onset or wind-only definitions, which may not necessarily capture the large-scale monsoonal conditions, and be amplified by short-term weather variability.

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Unique thermal mixing patterns in Lake Ontario revealed by novel year‐round observations of thermal stratification - Mathew Wells; Tim Johnson; Rylie Robinson; Jon Midwood; Yulu Shi; Sarah Larocque; Adam Eddie; Brian O'Malley; Kyle Morton; Dimitry Gorsky; Bruce Tufts (Limnology and Oceanography, 2025)
Year‐round records of thermal stratification in the Great Lakes are rare, and there are few observations of thermal stratification during winter. In this paper, we analyze temperature data from 13 temperature logger chains and from over 130 benthic acoustic receivers that were deployed across Lake Ontario for 2 yr. The timing and duration of the fall overturn correlate with the local average water depth, and shallow sites ( 100 m depths). Likewise, in spring, the shallow sites warm faster. Lake Ontario has partial ice cover, so wind‐driven mixing stirs the water column throughout winter, and inverse thermal stratification is largely absent. The depth‐averaged winter water temperatures vary between 0°C and 4°C, with the coldest temperatures (near 0.1°C) found in the shallow Kingston basin and warmest temperatures (near 4°C) at sites near the 244 m deep Rochester Basin. Lake Ontario appears to be a warm monomictic lake, rather than having a dimictic mixing pattern as previously described—there is no sustained ice cover or inverse stratification that inhibits vertical mixing in winter. Winter is a poorly understood season for many aquatic processes, including fish bioenergetics, fish distribution, biochemical processes, invertebrate distribution, and production. Moreover, the lack of knowledge of winter has hampered the use of correct initial conditions for running large lake hydrodynamic models.

Design and implementation of resistive grout for cross-borehole electrical imaging - Jonathan Thomle; Kelsey Peta; Lirong Zhong; Judy Robinson; Tim Johnson (Journal of Applied Geophysics, 2025)

Enabling the circular nitrogen economy with organic and organo-mineral fertilisers - Susanne Schmidt; Vithya Krishnan; Harshi Gamage; Michael Walsh; Tim Huelsen; Juliane Wolf; Peter Wadewitz; Paul Jensen; Bianca Das; Nicole Robinson (Nutrient Cycling in Agroecosystems, 2025)
The circular nutrient economy repurposes organic (formerly alive, containing organic carbon) and inorganic (mineral) recycled materials as fertilisers and soil ameliorants, and halving nitrogen (N) waste is a global goal. Our focus was unavoidable food waste and garden waste (FOGO food organics garden organics) as suitable feedstock for compost and use for cropping. We hypothesised that to realise benefits of compost, organic and organo-mineral fertilisers (OF/OMF) must be optimised for target crops and biophysical environments. We explored compost and organic recyclates (dried bacterial biomass PPB, chicken litter manure) as N sources for vegetable, fruit and grain crops in controlled experiments with single or combinations of contrasting N release and carbon-to-N ratios of 20, 13.5 (compost), 13.5 (poultry manure), 6.1 (PPB) and 0.5 (mineral N). With standardised N input (0.5–1 g N/pot and plant), compost as the sole N source resulted in less yield than all other N sources, while suitable mixtures of organic recyclates with/without added mineral N matched the yield of crops grown with mineral N. Adding 5% compost to sand growth substrate modulated crop growth and phenology, increased tillering and panicle production, or accelerated fruit ripening. This confirmed effects beyond nutrient supply, likely crop-growth modulating substances are present. Exploring effects of crop species, N source and water supply confirmed statistically significant interactions on yield, biomass and N use efficiency (NUE). This means a robust strategy for optimising OF/OMF is testing target crops with compost and recyclates to identify crop-specific responses. We recommend that applying such strategy allows manufacturers targeting N-efficient OF/OMF to service the expanding market for recyclate-based organo-mineral fertilisers and soil ameliorants for the circular N economy.

A guide to assess the use of gene editing in aquaculture - Nicholas A. Robinson; Tone‐Kari Knutsdatter Østbye; Anne H. Kettunen; Andrew Coates; Luke T. Barrett; Diego Robledo; Tim Dempster (Reviews in Aquaculture, 2024)
Aquaculture creates ‘aquatic foods’ such as fish, shellfish, and seaweeds that are critical for food security. Gene editing using CRISPR‐Cas9 has the potential to transform aquaculture by improving animal welfare, nutritional attributes, and farming efficiency, with benefits for environmental sustainability. However, gene editing also poses risks of harm via side effects on other important traits or genetic introgression into wild populations. Public acceptance of gene edited aquatic species will rapidly erode if risk mitigation is ineffective or not applied. Here, we review the benefits and risks for gene editing in aquaculture. A general framework for risk–benefit analysis of gene editing in aquaculture is proposed, incorporating nine key considerations: genetic impacts, ecological impacts, disease risk mitigation, nature of edit, supply chain environmental footprint, animal welfare, human nutrition, ethical business implications and impacts on local communities. When applied on a case‐by‐case basis, the framework will help identify how gene editing of a farmed species can most enhance production and nutritional benefits while minimising harms to animal welfare, the environment, and society.

Climate-smart fisheries: CO2 emissions reduction and food security are complementary - Nwamaka Okeke-Ogbuafor; Tim Gray; Sheku Kamara; Edward Sesay; Abdulai Dauda; Selina M Stead; Danielle Robinson; Kelechi Johnmary Ani (Marine Policy, 2024)

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

Occurrences of tropical, subtropical and rare marine fishes in Aotearoa New Zealand indicate biodiversity change - Irene Middleton; Malcolm Francis; J. David Aguirre; Carl Struthers; Thomas Trnski; Clinton Duffy; John Anderson; Mary Carney; Nathan Cox; Stephen Hemstalk; Blair Herbert; Craig Johnston; et al. (Journal of Biogeography, 2023)
Aim Climate change is driving biogeographic change globally, including poleward range shifts of species and the increasing abundance of rare species. We examine spatiotemporal patterns in the occurrences of tropical, subtropical and rare marine fishes in Aotearoa New Zealand to determine whether biodiversity change is occurring in this temperate region and to set a baseline for future monitoring of climate change impacts. Location Aotearoa New Zealand (NZ). Taxon Marine fishes. Methods We consolidated 100 years of unpublished records and citizen science sightings of tropical, subtropical and rare fishes to develop a focal species database for NZ. Using hotspot analysis, we identified geographic locations where the occurrence and diversity of focal species is greater than expected. We examine the spatiotemporal variation in hotspots by focal species lifestage, habitat and taxonomic family. Results Focal species occurrences and diversity in NZ have increased. We present 17 new‐to‐NZ marine fish species, and a new‐to‐NZ family. Focal species now account for 6.5% of pelagic fishes and 17.3% of benthic fishes in NZ. The northeast of the North Island (Te Ika‐a‐Māui) was a consistent hotspot of focal species occurrences and diversity. Hotspots of mature and pelagic fish occurrences appeared further south than juvenile and benthic species occurrences. Families with tropical affinities (Labridae and Pomacentridae) were restricted to northeastern NZ whereas hotspots of families with temperate affinities (i.e. Cheilodactylidae) extended into the South Island (Te Waipounamu). Main Conclusions Tropical, subtropical and rare fishes are a major component of the fish biodiversity in temperate NZ, and their occurrences and diversity has increased over the past half‐century. Northeastern NZ consistently has the highest occurrence rate and diversity of warmer‐water fishes. Our study demonstrates the value in consolidating citizen scientist observations to detect biodiversity change, and to inform current baselines and future monitoring of climate‐related biodiversity change.

Using fish swimming ability to refine criteria for fishway construction in Myanmar - John Conallin; Nyi Nyi Tun; Aye Myint Swe; Lee J. Baumgartner; Zau Lunn; Martin Mallen-Cooper; Tim Marsden; Nathan Ning; Wayne Robinson; Lalantha Senevirathna; Peter Thew (Fisheries Research, 2023)

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Long-Term Drought and Warming Alter Soil Bacterial and Fungal Communities in an Upland Heathland - Fiona M. Seaton; Sabine Reinsch; Tim Goodall; Nicola White; Davey L. Jones; Robert I. Griffiths; Simon Creer; Andy Smith; Bridget A. Emmett; David A. Robinson (Ecosystems, 2022)
The response of soil microbial communities to a changing climate will impact global biogeochemical cycles, potentially leading to positive and negative feedbacks. However, our understanding of how soil microbial communities respond to climate change and the implications of these changes for future soil function is limited. Here, we assess the response of soil bacterial and fungal communities to long-term experimental climate change in a heathland organo-mineral soil. We analysed microbial communities using Illumina sequencing of the 16S rRNA gene and ITS2 region at two depths, from plots undergoing 4 and 18 years of in situ summer drought or warming. We also assessed the colonisation of Calluna vulgaris roots by ericoid and dark septate endophytic (DSE) fungi using microscopy after 16 years of climate treatment. We found significant changes in both the bacterial and fungal communities in response to drought and warming, likely mediated by changes in soil pH and electrical conductivity. Changes in the microbial communities were more pronounced after a longer period of climate manipulation. Additionally, the subsoil communities of the long-term warmed plots became similar to the topsoil. Ericoid mycorrhizal colonisation decreased with depth while DSEs increased; however, these trends with depth were removed by warming. We largely ascribe the observed changes in microbial communities to shifts in plant cover and subsequent feedback on soil physicochemical properties, especially pH. Our results demonstrate the importance of considering changes in soil microbial responses to climate change across different soil depths and after extended periods of time.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Evolution of salmon lice in response to management strategies: a review - Andrew Coates; Ben L. Phillips; Samantha Bui; Frode Oppedal; Nick A. Robinson; Tim Dempster (Reviews in Aquaculture, 2021)
Ectoparasitic salmon lice ( Lepeophtheirus salmonis ) present a major challenge to Atlantic salmon ( Salmo salar ) aquaculture. The demand for effective louse control has produced diverse management strategies. These strategies essentially impose novel selection pressures on parasite populations, driving the evolution of resistance. Here we assess the potential for salmon lice to adapt to current prevention and control methods. Lice have evolved resistance to at least four of five chemical therapeutants, and use of these chemicals has declined significantly in recent years. The industry has shifted to alternative non‐chemical approaches, yet lice may adapt to these as well. Early research suggests that phenotypic variation exists in the louse population upon which non‐chemical selection pressures could act and that this variation may have a genetic basis. From the existing evidence, as well as an examination of evolutionary processes in other relevant parasite and pest systems, we conclude that the evolution of non‐chemical resistance is an emergent concern that must be considered by the industry. We recommend areas for focused research to better assess this risk. It is also important to determine whether phenotypic shifts in response to non‐chemical selection may shift the ecological niche of the parasite, as this may have cascading effects on wild salmon populations. We also recommend further research to identify strategy combinations that have antagonistic selective effects that slow louse evolution and those with synergistic effects that should be avoided. Greater understanding of evolutionary processes can inform aquaculture policies that counteract the rise of resistant parasite populations.

Prevention not cure: a review of methods to avoid sea lice infestations in salmon aquaculture - Luke T. Barrett; Frode Oppedal; Nick Robinson; Tim Dempster (Reviews in Aquaculture, 2020)
The Atlantic salmon aquaculture industry still struggles with ectoparasitic sea lice despite decades of research and development invested into louse removal methods. In contrast, methods to prevent infestations before they occur have received relatively little research effort, yet may offer key benefits over treatment‐focused methods. Here, we summarise the range of potential and existing preventative methods, conduct a meta‐analysis of studies trialling the efficacy of existing preventative methods and discuss the rationale for a shift to the prevention‐focused louse management paradigm. Barrier technologies that minimise host–parasite encounter rates provide the greatest protection against lice, with a weighted median 76% reduction in infestation density in cages with plankton mesh ‘snorkels’ or ‘skirts’, and up to a 100% reduction for fully enclosed cages. Other methods such as geographic spatiotemporal management, manipulation of swimming depth, functional feeds, repellents and host cue masking can drive smaller reductions that may be additive when used in combination with barrier technologies. Finally, ongoing development of louse‐resistant salmon lineages may lead to long‐term improvements if genetic gain is maintained, while the development of an effective vaccine remains a key target. Preventative methods emphasise host resistance traits while simultaneously reducing host–parasite encounters. Effective implementation has the potential to dramatically reduce the need for delousing and thus improve fish welfare, productivity and sustainability in louse‐prone salmon farming regions.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Endophytic bacterial community composition in wheat (Triticum aestivum) is determined by plant tissue type, developmental stage and soil nutrient availability - Rebekah J. Robinson; Bart A. Fraaije; Ian M. Clark; Robert W. Jackson; Penny R. Hirsch; Tim H. Mauchline (Plant and Soil, 2016)

The extremely long-runout Komansu rock avalanche in the Trans Alai range, Pamir Mountains, southern Kyrgyzstan - Tom R. Robinson; Tim R. H. Davies; Natalya V. Reznichenko; Gregory P. De Pascale (Landslides, 2015)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.

SoilTrEC: a global initiative on critical zone research and integration - Manoj Menon; Svetla Rousseva; Nikolaos P. Nikolaidis; Pauline van Gaans; Panos Panagos; Danielle Maia de Souza; Kristin Vala Ragnarsdottir; Georg J. Lair; Liping Weng; Jaap Bloem; Pavel Kram; Martin Novak; et al. (Environmental Science and Pollution Research, 2014)

Estimating the annual number of breeding attempts from breeding dates using mixture models - Thomas Cornulier; David A. Elston; Peter Arcese; Tim G. Benton; David J.T. Douglas; Xavier Lambin; Jane Reid; Robert A. Robinson; William J. Sutherland (Ecology Letters, 2009)
Well‐established statistical methods exist to estimate variation in a number of key demographic rates from field data, including life‐history transition probabilities and reproductive success per attempt. However, our understanding of the processes underlying population change remains incomplete without knowing the number of reproductive attempts individuals make annually; this is a key demographic rate for which we have no satisfactory method of estimating. Using census data to estimate this parameter from requires disaggregating the overlying temporal distributions of first and subsequent breeding attempts. We describe a Bayesian mixture method to estimate the annual number of reproductive attempts from field data to provide a new tool for demographic inference. We validate our method using comprehensive data on individually‐marked song sparrows Melospiza melodia , and then apply it to more typical nest record data collected over 45 years on yellowhammers Emberiza citrinella . We illustrate the utility of our method by testing, and rejecting, the hypothesis that declines in UK yellowhammer populations have occurred concurrently with declines in annual breeding frequency.

Lag Effects in the Impacts of Mass Coral Bleaching on Coral Reef Fish, Fisheries, and Ecosystems - NICHOLAS A. J. GRAHAM; SHAUN K. WILSON; SIMON JENNINGS; NICHOLAS V. C. POLUNIN; JAN ROBINSON; JUDE P. BIJOUX; TIM M. DAW (Conservation Biology, 2007)
Recent episodes of coral bleaching have led to wide‐scale loss of reef corals and raised concerns over the effectiveness of existing conservation and management efforts. The 1998 bleaching event was most severe in the western Indian Ocean, where coral declined by up to 90% in some locations. Using fisheries‐independent data, we assessed the long‐term impacts of this event on fishery target species in the Seychelles, the overall size structure of the fish assemblage, and the effectiveness of two marine protected areas (MPAs) in protecting fish communities. The biomass of fished species above the size retained in fish traps changed little between 1994 and 2005, indicating no current effect on fishery yields. Biomass remained higher in MPAs, indicating they were effective in protecting fish stocks. Nevertheless, the size structure of the fish communities, as described with size‐spectra analysis, changed in both fished areas and MPAs, with a decline in smaller fish ( 45 cm). We believe this represents a time‐lag response to a reduction in reef structural complexity brought about because fishes are being lost through natural mortality and fishing, and are not being replaced by juveniles. This effect is expected to be greater in terms of fisheries productivity and, because congruent patterns are observed for herbivores, suggests that MPAs do not offer coral reefs long‐term resilience to bleaching events. Corallivores and planktivores declined strikingly in abundance, particularly in MPAs, and this decline was associated with a similar pattern of decline in their preferred corals. We suggest that climate‐mediated disturbances, such as coral bleaching, be at the fore of conservation planning for coral reefs.

GIS and multiple-criteria evaluation for the optimisation of tsetse fly eradication programmes - Elias Symeonakis; Tim Robinson; Nick Drake (Environmental Monitoring and Assessment, 2007)

Bacterial diversity is determined by volume in membrane bioreactors - Christopher J. Van Der Gast; Bruce Jefferson; Elizabeth Reid; Tim Robinson; Mark J. Bailey; Simon J. Judd; Ian P. Thompson (Environmental Microbiology, 2006)
Summary It has been proposed that established models and theories developed in classical ecology could be employed to greatly improve the optimization of wastewater treatment plants (WWTP) by placing the microbiological component onto a model‐predictive basis. In particular, this could be achieved by better understanding bacterial community assembly and development. The species–area relationship is one of the oldest biological laws and has been used to describe spatial diversity patterns in contiguous habitats and on islands. In the current study, bacterial communities in seven membrane bioreactors (MBR), of increasing size, located across the UK were sampled. A significant linear relationship between bacterial taxa richness and reactor size was observed and was similar to classical species–area relationships of larger organisms colonizing oceanic islands. Rank‐abundance plots revealed a gradient of greater evenness in community structure as MBR volume increased. Application of the Raup and Crick probability‐based similarity index indicated a strong role for dispersal in MBR colonization and community structure. Our findings demonstrate that the MBR sampled behaved like islands with respect to bacterial colonization in accordance with the theory of island biogeography. In addition this study provides further evidence that biodiversity at the bacterial level is more similar to that of animals and plants than previously postulated.

Improving the Evaluation of Conservation Programs - Devra G. Kleiman; Richard P. Reading; Brian J. Miller; Tim W. Clark; J. Michael Scott; John Robinson; Richard L. Wallace; Robert J. Cabin; Fred Felleman (Conservation Biology, 2000)
The evaluation of conservation programs is rare but increasingly important in improving their effectiveness. Regular evaluations of conservation programs and the implementation of recommendations resulting from such assessments are infrequent because of resistance by participants and lack of funding. Evaluations may be internal or external, depending on the purpose of the review and how broadly it is focused. We strongly recommend external peer review of long‐term complex conservation programs every 5 years, supported by more frequent (annual) internal reviews. Criteria for success must encompass both biological and social measures and include learning and the application of new knowledge to management. Evaluations must also go beyond monitoring to assess the value of the program. We emphasize the need to include the organization and function of a conservation program (the process) in any evaluation in addition to substantive criteria for success, which usually involve biological measures (numbers). A dysfunctional program organization and process can as effectively cripple a conservation effort as can a major biological catastrophe. We provide examples of different types of conservation program evaluations, including moderated workshops and case‐study analysis, and provide advice on the logistics and organization of the review, emphasizing the importance of the evaluation process itself to a successful outcome. One important aspect of an evaluation is having an individual with leadership ability and considerable expertise to organize the format and oversee the review process itself. Second, it is essential at the outset to ensure agreement among the program participants and the review committee on the goals and objectives of the conservation program, what is to be evaluated, and the criteria for defining success. Finally, the best evaluations are inclusive and involve all participants and stakeholders.